2020
DOI: 10.3389/fnana.2020.00030
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility and Vulnerability of Brain Cells in C57BL/6 Mouse to Mitochondrial Dysfunction Induced by Short-Term Cuprizone Exposure

Abstract: Cuprizone (CPZ) is a chemical chelator toxic to mitochondria of cells. While inducing oligodendrocyte (OL) loss and demyelination, CPZ caused no fatal damage to the other brain cells (neurons, astrocytes, and microglia) in previous studies, suggesting differential susceptibility and vulnerability of brain cells to the CPZ intoxication. To demonstrate this interpretation, C57BL/6 mice were fed rodent chow without or with CPZ (0.2%, w/w) for 7 days. One day later, mitochondrial function of brain cells was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…ROS also directly induce oligodendrocyte death (e.g., ferroptosis [ 101 ]). Staining the corpus callosum with 8-OhdG reveals that oligodendrocytes contain oxidized nucleotides – an indication of elevated ROS [ 123 ] – after 1 week of cuprizone treatment [ 124 ]. Oligodendrocytes are particularly sensitive to ROS given their heightened storage of Fe 3+ within ferritin.…”
Section: Main Textmentioning
confidence: 99%
“…ROS also directly induce oligodendrocyte death (e.g., ferroptosis [ 101 ]). Staining the corpus callosum with 8-OhdG reveals that oligodendrocytes contain oxidized nucleotides – an indication of elevated ROS [ 123 ] – after 1 week of cuprizone treatment [ 124 ]. Oligodendrocytes are particularly sensitive to ROS given their heightened storage of Fe 3+ within ferritin.…”
Section: Main Textmentioning
confidence: 99%
“…These results suggest that brain neurons are more resistant to stress-induced mitochondrial damage relative to OLs. This suggestion has been elegantly tested true in a very recent study of our team, which showed that brain neurons are most sensitive but most resistant to mitochondria oxidative stress whereas mature OLs are sensitive and most vulnerable 57 . Relevantly, patients with Canavan's disease show NAA accumulation along with myelin defect due to the deficiency of ASPA 58 .…”
Section: Discussionmentioning
confidence: 95%
“…In fact, differential susceptibility of neurons and glia against oxidative or mitochondrial damage in the aged or diseased brains has been the subject of intensive research [ 48 , 49 ]. In a very recent study, Luo et al, (2020) demonstrated a differential vulnerability, in terms of mitochondrial dysfunction, of brain cells of C57BL/6 mice subjected to short-term CPZ intoxication; the more efficient REDOX system of neurons makes them more resistant than OLGs to oxidative stress and mitochondrial damage [ 50 ]. The results show that CPZ alters energetic metabolism but why OLGs are more sensitive to these alterations is still an open question.…”
Section: Discussionmentioning
confidence: 99%